Genetic and Molecular Relationship among Cucumeropsis Mannii Naudin using RAPD Marker - Joseph, Olawuyi Odunayo; Iyanu, Adedeji (The International Journal of Biotechnology, 2020)
Twenty-four accessions of Cucumeropsis mannii obtained from National Centre for Genetic Resources and Biotechnology and some markets from Seven Local Governments in Ibadan were evaluated for genetic relationship using RAPD marker. The field experiment was conducted at the research farm of the Department of Botany, University of Ibadan and arranged in a Completely Randomized Design with four replicates. The molecular experiment was done at International Institute of Tropical Agriculture, Ibadan. The mean square interaction of accessions and their Local governments were significantly (P<0.01) higher for growth, agronomic and yield characters. Accession C3 from Mokola performed best in morphological and yield characters while NGB/01611, NG/TOLO2/11/150 and NG/AA/03/11/040 had the least. Plant height is positively associated with number of leaves (r=0.73), leaf width(r=0.72), number of fruits (r=0.52) and leaf length (0.51). The number of leaves is positively related with leaf width, dry shoot weight, dry leaf weight and dry root weight at r= 0.94, 0.74, 0.73, 0.63 respectively, while dry root weight and fruit weight (r=0.73) are positively related. Two cluster groups were delineated from twenty-four accessions of C. mannii in the dendogram. Cluster 1 constitutes the largest 17 cluster groups and different sub-groups. Accession C12 from Lalupon had highest genomic DNA concentration of 1.89 ug, while highest total volume of 827.9 ul was recorded for C15 from Olodo. Primer OPHO9 had highest allele diversity and polymorphic information content at 0.93 and 92.23% respectively. Therefore, variability among accessions of C. mannii could promote the conservation of C. mannii for genetic improvement program.